Nine Decades of Radiology in Thailand - Sukthomya, Vimol (The Journal of Chulabhorn Royal Academy, 2020)
It may be addressed that Radiology is related to all branches of medical sciences and public health. This is because Radiology contributes to diagnostic accuracy, makes treatment planning comprehensive and results in the betterment of the patients. In Thailand Radiology has had a long and continuous history of development. This academic article excellently summarized historical events as well as the profiles of key founders of Radiology in Thailand. Readers should not only be able to understand the many aspects of radiology studies but also be informed for the purpose of further development in the future.